Correlation between porosity and permeability of stainless steel filters with gradient porosity produced by SLS/SLM. Issue 1 (15th August 2019) - Fogliatto, Aloysio Arthur Becker; Ahrens, Carlos Henrique; Wendhausen, Paulo Antônio Pereira; Santos, Edson Costa; Rodrigues, Daniel
Abstract : Purpose: Porous structures have been widely used in filtration, medical implants and aerospace field. In the filtration field, the study of permeability of the porous structures is of great importance. This paper aims to study the influence of selective laser sintering/melting (SLS/SLM) process parameters on porosity and permeability of stainless steels filters with gradient porosity (FGM). Design/methodology/approach: AISI 316L stainless steel powder was used to manufacture FGM filters by varying the hatch distance while other process parameters were fixed. The relationship between porosity and permeability of such FGM filters was investigated by means of Archimedes' and Forchheimer's laws. The gradient of porosity was also analyzed by means of micro-computed tomography. Findings: The results have confirmed the ability of SLS/SLM in controlling porosity of the final product by varying the hatch distance. Further, the results allow to assume that FGM filters will have particle retention capacity related to lowest porosity value (which in turn is associated with the lowest hatch distance value used), while it will work at lower pressure drops – or at higher flow rates for equal pressure drop – when compared to a filter without gradient porosity. Originality/value: Some research found in recent literature has showed the relationship between SLS/SLM process parameters and permeability of stainless steel porous structures. However, this paper fulfils the need to understand the relationship between SLS/SLM process parameters, porosity and permeability behavior of functionally graded porous structures (FGM filters).